Imagining Other People’s Experiences in a Person with Impaired Episodic Memory: The Role of Personal Familiarity - Rabin, Jennifer S.; Carson, Nicole; Gilboa, Asaf; Stuss, Donald T.; Rosenbaum, R. Shayna (Frontiers in Psychology, 2013)
Difficulties remembering one’s own experiences via episodic memory may affect the ability to imagine other people’s experiences during theory of mind (ToM). Previous work shows that the same set of brain regions recruited during tests of episodic memory and future imagining are also engaged during standard laboratory tests of ToM. However, hippocampal amnesic patients who show deficits in past and future thinking, show intact performance on ToM tests, which involve unknown people or fictional characters. Here we present data from a developmental amnesic person (H.C.) and a group of demographically matched controls, who were tested on a naturalistic test of ToM that involved imagining other people’s experiences in response to photos of personally familiar others (‘pToM’ condition) and unfamiliar others (‘ToM’ condition). We also included a condition that involved recollecting past experiences in response to personal photos (‘EM’ condition). Narratives were scored using an adapted autobiographical interview scoring procedure. Due to the visually rich stimuli, internal details were further classified as either descriptive (i.e., details that describe the visual content depicted in the photo) or elaborative (i.e., details that go beyond what is visually depicted in the photo). Relative to controls, H.C. generated significantly fewer elaborative details in response to the pToM and EM photos and an equivalent number of elaborative details in response to the ToM photos. These data converge with previous neuroimaging results showing that the brain regions underlying pToM and episodic memory overlap to a greater extent than those supporting ToM. Taken together, these results suggest that detailed episodic representations supported by the hippocampus may be pivotal for imagining the experiences of personally familiar, but not unfamiliar, others.